The spectrum problem for the cubic graphs of order 8 - Peter Adams (2018)
© 2018 Charles Babbage Research Centre. All rights reserved. We show that if G is a cubic graph of order 8, then there exists a G-decomposition of Kv if and only if v = 1 or 16 (mod 24).